The Dynamics of Federalism: Examining the Interplay between Federal, States and Local Level Governments in Nepal - Mallik, Sabita Kumari (Political Science Journal, 2025)
This study examines the complex interrelationship between state and local level government structures and federalism. The study aims to clarify the intergovernmental federal frameworks between state and local governments through a comparative analysis of federal systems in the USA, Switzerland and India along with Nepal. The study investigates how federalism affects the effectiveness of state government, service provision, financial independence, and democratic engagement. It also looks at the opportunities and difficulties that result from the interaction of federal, state and local authorities, illuminating topics like intergovernmental relations, resource distribution, and policy implementation. Through the integration of theoretical understanding and qualitative data, this article advances our comprehension of the intricate dynamics present in federal systems and their consequences for state and local governance.